2013
DOI: 10.1016/j.asr.2012.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the IRI-2007 model for equatorial topside ion density in the African sector for low and extremely low solar activity

Abstract: 11The recent availability of new data sets during the recent extreme solar minimum 12 provides an opportunity for testing the performance of the International Reference

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…The discrepancies occur primarily during daytime and at low/equatorial latitudes and diminish during nighttime. Klenzing et al (2011Klenzing et al ( , 2013) confirmed these results with data from the Retarding Potential Analyzer (RPA) of the Coupled Ion-Neutral Dynamics Investigation (CINDI) suite of instruments that flew on the Communication/Navigation Outage Forecast System (C/NOFS) satellite during this time period covering the altitude range 400-850 km. They found that the overestimation increases with altitude and that in the latitude range covered by the satellite (dip latitude = À30°to 6°) the largest discrepancies are observed near the crests of the Equatorial Ionization Anomaly (EIA).…”
Section: Introductionmentioning
confidence: 61%
“…The discrepancies occur primarily during daytime and at low/equatorial latitudes and diminish during nighttime. Klenzing et al (2011Klenzing et al ( , 2013) confirmed these results with data from the Retarding Potential Analyzer (RPA) of the Coupled Ion-Neutral Dynamics Investigation (CINDI) suite of instruments that flew on the Communication/Navigation Outage Forecast System (C/NOFS) satellite during this time period covering the altitude range 400-850 km. They found that the overestimation increases with altitude and that in the latitude range covered by the satellite (dip latitude = À30°to 6°) the largest discrepancies are observed near the crests of the Equatorial Ionization Anomaly (EIA).…”
Section: Introductionmentioning
confidence: 61%
“…EUV and X-ray radiation were exceptionally reduced compared with the previous solar minimum. As a result, the terrestrial thermosphere at high altitude was cooler and lower in density than expected [Solomon et al, 2010[Solomon et al, , 2011[Solomon et al, , 2013, and in general, the low-density values measured either from space or from the ground were overestimated by the ionospheric models for local and global conditions [e.g., Sethi et al, 2011;Adewale et al, 2012;Klenzing et al, 2013;Yue et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of these model options are necessary in order to find out which of them can provide the best representation of the current ionospheric conditions. Moreover, corrections of the IRI model are still the main efforts of many researchers (e.g., Huang and Reinisch, 2001;Bilitza et al, 2006;Richards et al, 2010;Zhang et al, 2010;Bilitza et al, 2011;Gakin et al, 2012;Nsumei et al, 2012;Klenzing et al, 2013;Bilitza et al, 2014;Verhulst and Stankov, 2014;Wang et al, 2015). Coisson et al (2002Coisson et al ( , 2006 compared IRI and NeQuick model with ISIS 2 topside electron density profiles to identify and analyze the weak points in their topside formulation.…”
Section: Introductionmentioning
confidence: 99%